How not to be wrong the power of mathematical thinking - Ellenberg, Jordan 1971- (New York The Penguin Press, 2014)
"In How Not to Be Wrong, Jordan Ellenberg shows us that math isn't confined to abstract incidents that never occur in real life, but rather touches everything we do--the whole world is shot through with it. Math allows us to see the hidden structures underneath the messy and chaotic surface of our world. It's a science of not being wrong, hammered out by centuries of hard work and argument. Armed with the tools of mathematics, we can see through to the true meaning of information we take for granted: How early should you get to the airport? What does "public opinion" really represent? Why do tall parents have shorter children? Who really won Florida in 2000? And how likely are you, really, to develop cancer? How Not to Be Wrong presents the surprising revelations behind all of these questions and many more, using the mathematician's method of analyzing life and exposing the hard-won insights of the academic community to the layman--minus the jargon. Ellenberg pulls from history as well as from the latest theoretical developments to provide those not trained in math with the knowledge they need. "-- Provided by publisher.
When am I going to use this? -- Linearity. Less like Sweden ; Straight locally, curved globally ; Everyone is obese ; How much is that in dead Americans? ; More pie than plate -- Inference. The Baltimore stockbroker and the Bible Code ; Dead fish don't read minds ; Reductio ad unlikely ; The international journal of haruspicy ; Are you there, God? It's me, Bayesian inference -- Expectation. What to expect when you're expecting to win the lottery ; Miss more planes! ; Where the train tracks meet -- Regression. The triumph of mediocrity ; Galton's ellipse ; Does lung cancer make you smoke cigarettes? -- Existence. There is no such thing as public opinion ; "Out of nothing I have created a strange new universe" -- How to be right.
Includes bibliographical references (pages 443-457) and index.
Keywords: Mathematics -- Miscellanea; Mathematical analysis -- Miscellanea